2015
DOI: 10.1891/1946-6560.6.3.273
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes and Process Improvement Project: Batterers’ Intervention Program Evaluation Comparing English-Language and Spanish-Language Offenders

Abstract: This study was a longitudinal, naturalistic comparison of treatment completion and reoffense rates for two groups of offenders convicted of domestic violence (DV): Seventy-five men attending Spanish-language classes and 75 men attending English-language classes. Participant-specific background and psychosocial information, as well as alcohol and drug use, were assessed for influencing program success and DV reoffense. Overall, men who completed DV classes were less likely to reoffend than those who did not. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Research by Trebow, Berkanovic, and Harada (2015) found that there was a 50% split between men attending Spanish language DVIPV classes and those attending English language DVIPV classes, with a total number of 150 participants. Participant-specific background and psychosocial information, as well as alcohol and drug use were assessed for influencing program success and DVIPV re-offense.…”
Section: Participants Within the Research Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Trebow, Berkanovic, and Harada (2015) found that there was a 50% split between men attending Spanish language DVIPV classes and those attending English language DVIPV classes, with a total number of 150 participants. Participant-specific background and psychosocial information, as well as alcohol and drug use were assessed for influencing program success and DVIPV re-offense.…”
Section: Participants Within the Research Bodymentioning
confidence: 99%
“…Participant-specific background and psychosocial information, as well as alcohol and drug use were assessed for influencing program success and DVIPV re-offense. According to Trebow, Berkanovic, and Harada (2015), the rate of English-language participants who had new DVIPV convictions was three times the rate of Spanish-language participants. I found this very interesting and wondered if this was as a result of culturally specific/culturally acknowledged Latino DVIPV education related to program delivery within this research.…”
Section: Participants Within the Research Bodymentioning
confidence: 99%